2016
DOI: 10.1016/j.jvs.2016.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after open and endovascular elective repair for infrarenal abdominal aortic aneurysms

Abstract: Objective: The aim of this study was to evaluate the incidence of acute kidney injury (AKI) after open and endovascular abdominal aortic aneurysm repair according to the Aneurysm Renal Injury Score classification. Methods: We retrospectively evaluated 431 patients undergoing elective open aortic repair (OAR; n [ 285) or endovascular repair (n [ 146) for infrarenal aortic aneurysm. All data regarding preoperative and postoperative serum creatinine concentrations and postoperative outcomes were assessed. Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…Using ARISe, Castagno et al recently reported that the incidence of postoperative AKI was 26.3% (75/285) and 5.5% (8/146) in patients who underwent elective OAR and EVAR, respectively. 5 ) In a large-scale study, Zarkowsky et al collected data on preoperative and postoperative serum creatinine concentration from the Vascular Quality Initiative database. 7 ) They reported that only 2.9% of the 14,475 non-hemodialysis patients who underwent elective EVAR developed AKI, which was defined as an increase in serum creatinine concentration>0.5 mg/dL, and 0.4% newly required hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using ARISe, Castagno et al recently reported that the incidence of postoperative AKI was 26.3% (75/285) and 5.5% (8/146) in patients who underwent elective OAR and EVAR, respectively. 5 ) In a large-scale study, Zarkowsky et al collected data on preoperative and postoperative serum creatinine concentration from the Vascular Quality Initiative database. 7 ) They reported that only 2.9% of the 14,475 non-hemodialysis patients who underwent elective EVAR developed AKI, which was defined as an increase in serum creatinine concentration>0.5 mg/dL, and 0.4% newly required hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative renal dysfunction was reported to increase the risk of AKI after elective surgery for AAA. 3 , 5 , 10 ) Tang et al reported that preoperative eGFR >60 mL/min/1.73 m 2 was associated with a 0.957-fold decreased risk of AKI in combined patient analysis for both OAR and EVAR. 3 ) Castagno et al similarly reported that chronic renal disease, defined as a preoperative serum creatinine concentration>1.2 mg/dL, was associated with a 2.53-fold increased risk of AKI in combined patient analysis for both OAR and EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Suprarenal clamping implies renal ischemia, which may increase in-hospital mortality 1) and the incidence of postoperative acute kidney injury (AKI). [2][3][4][5][6][7] Postoperative AKI is a common, but serious, complication of aortic repair for AAA because it may increase early mortality 8,9) and patients hospital stay 10,11) ; it may also affect late survival. 8,12,13) Although much attention to date has been given to this complication, research into AKI following AAA repair remains challenging due to the fact that AAAs differ from each other morphologically and clinically.…”
Section: Introductionmentioning
confidence: 99%